Concept of a Novel Energy Management System for Microgrids and Energy Communities - Lóránt Kovács; Bernadett Rádli-Burján; Balázs Vehovszky; Zoltán Weltsch; Ferenc Magyar (Chemical Engineering Transactions)
The green transition of the global energy system presents considerable economic and technological challenges. One of them is the local and temporal difference between available energy sources and energy demand. To overcome this problem, two conceptual solutions can be considered: one is the use of an energy carrier that is suitable for medium- and long-term storage and safe transportation of energy. Carbon-based fuels (or novel alternatives, like hydrogen) or electric energy are the solutions currently used; however, we are facing their environmental or technical limitations. The other one is the synchronisation and intelligent control of sources and consumers, which could significantly decrease the storage and transportation needs. The current article discusses such a solution through a conceptual example. For the conceptual design of an advanced energy management system, the main related system elements shall be defined, and characteristic properties must be assigned to them. Input parameters for the energy management strategy must be given and prioritised. All this information enables the system to calculate and define instantaneous operational optimum. Also, an intelligent control system should take time-dependent processes and parameters into account, which can be deterministic or stochastic. As a result of this study, an energy management system concept that is based on realistic components and use cases is proposed, and its applicability to a local energy community is evaluated.